Exploratory Analysis of Entrepreneurship Education in the Jamshoro Public Universities: A Descriptive Study - Aasma Solangi; Adnan Pitafi (NAROTAMA UNIVERSITY, Indonesia, 2022)
The purpose of this study is to explore entrepreneurship education courses offered by public universities of the Jamshoro higher education institutions (HEIs). It examines the scope and the existing status of entrepreneurship in the Jamshoro public universities. Data were based on secondary data taken from official websites, prospectus, departmental reports and universities’ policy documents of the public universities of the Jamshoro Higher, included three public universities by examining their curricula and exploring the status of entrepreneurship of the selected sample from these universities. The results of this study indicated the public universities of the Jamshoro higher education city, just one core course on entrepreneurship was offered to some departments. Furthermore entrepreneurship programs were extremely rare. As a result, this research may encourage policymakers and universities to develop an effective and appropriate syllabus to fill the gap in existing curriculum of not only entrepreneurship but other courses as well.